Mycorrhiza (VAM) Biofertilizer for the future - Jaga, P K; Upadhyay, V B (Indian Farming, 2018)
Based on above information, it is summerised that inoculation of plans with VAM fungi, improved nutrient and water absorption, enhances input use efficiency, crop quality and overall soil quality and led to nutrient economy.VAM fungi also confer other associated benefits on plants. Such as increased resistance to disease, drought, soil salinity and also enhance N-fixation in legumes as such, proves magical fungi in soil plant system and it is said that there is a biofertilizer which may be useful for future. The mycorrhizae fungi carry out its functions by expanding surface area of plant root system by 10- to 1,000-folds into the soil through their ramifying hyphae, thereby increasing their exploratory area for harnessing phosphorus others nutrient and water. Further, VAM fungi solubilize inorganic forms of nutrients through release of low molecular weight organic acids (oxalic malic acid etc.) Further, through secretion of a number of enzymes (chitinase, peroxidase, cellulose, protease, phosphatase etc.)VAM fungi attack on complex organic compounds converting theminto simple ones that can be absorbed and used by fungi/host plants to meet their energy needs for growth and reproduction.